Molecules from nature: Reconciling biodiversity conservation and global healthcare imperatives for sustainable use of medicinal plants and fungi. Issue 5 (29th September 2020) - Howes, Melanie‐Jayne R.; Quave, Cassandra L.; Collemare, Jérôme; Tatsis, Evangelos C.; Twilley, Danielle; Lulekal, Ermias; Farlow, Andrew; Li, Liping; Cazar, María‐Elena; Leaman, Danna J.; Prescott, Thomas A. K.; Milliken, William; et al.
Societal Impact Statement: Plants and fungi have provided, or inspired, key pharmaceuticals for global health challenges, including cancer, heart disease, dementia, and malaria, and are valued as traditional medicines worldwide. Global demand for medicinal plants and fungi has threatened certain species, contributing to biodiversity loss and depletion of natural resources that are important for the health of humanity. We consider the evolving role of plants and fungi in global healthcare as new challenges to human health and to biodiversity arise. We present current and emerging scientific approaches, to uncover and preserve nature‐based health solutions for the future, through harmonization with biodiversity conservation strategies. Summary: Non‐communicable diseases, including cardiovascular disease, cancer, and diabetes, are the main causes of deaths globally, and communicable diseases such as malaria and tuberculosis affect billions of people. Plants and fungi have provided key pharmaceuticals in our armory against these global health challenges, while in some regions of the world, they continue to have a central role in healthcare systems as traditional medicines. Consequently, global demand for plants and fungi in healthcare has threatened certain medicinal species, and is a driving factor in biodiversity loss. Yet the future of therapeutics from nature is evolving. Scientific advances are enabling the untapped potential of the world's plants and fungi to be explored for their medicinal value, and to reveal other roles they may have for improving health and well‐being; this demonstrates the value of natural capital as an incentive for biodiversity conservation. Emerging technologies also offer new hope for safeguarding essential medicines for the future, by revealing more sustainable solutions for sourcing key natural products. This review discusses recent developments and future approaches for the discovery of natural products as medicines, for health and well‐being, and strategies to harmonize the therapeutic use of biodiversity with its proactive conservation through nature‐based solutions. Abstract : Plants and fungi have provided, or inspired, key pharmaceuticals for global health challenges, including cancer, heart disease, dementia, and malaria, and are valued as traditional medicines worldwide. Global demand for medicinal plants and fungi has threatened certain species, contributing to biodiversity loss and depletion of natural resources that are important for the health of humanity. We consider the evolving role of plants and fungi in global healthcare as new challenges to human health and to biodiversity arise. We present current and emerging scientific approaches, to uncover and preserve nature‐based health solutions for the future, through harmonization with biodiversity conservation strategies.